Anti-dazzle antireflection film
By setting up a fill layer on the anti-glare layer, the fill layer is used to fill the concave and convex structure of the anti-glare layer, the problem of high surface roughness of the existing anti-glare film is solved, the wear resistance and easy cleaning are improved, and the product's Service life.
Patent Information
- Application Number
- CN202421298046.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2034-06-07
AI Technical Summary
The existing anti-glare films can easily lead to an increase in surface roughness during processing, thereby reducing wear resistance and easy cleaning.
A fill layer is provided on the anti-glare layer, which is used to fill the concave and convex structure of the anti-glare layer, thereby reducing the surface roughness of the entire film.
By adding the fill layer, the film's wear resistance and easy cleaning are improved, the product's use scenarios are widened and the product's service life is extended.
Smart Images

Figure CN222506589U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of optical films, in particular to an anti-glare and anti-reflection film. Background Art
[0002] In recent years, with the rapid development of electronic information technology and the popularization of the concept of intelligence, electronic devices with different functions have penetrated into all aspects of people's work and life, and more and more electronic devices need to have independent operating systems and displays. People use displays in different scenarios, and many problems have emerged that need to be solved. In order to adapt to the increasingly complex use environment and meet the gradually growing visual requirements, display-related technologies have developed rapidly, and related industries have become an important part of the electronic equipment industry.
[0003] One of the most common problems people encounter when using display devices is glare caused by improper brightness distribution in the field of view or large changes in brightness in a short period of time. Glare is a visual condition. When strong ambient light, such as the sun or lamplight, shines on the screen surface and reflects into the user's eyes, it is difficult for the user to observe the weak light on the screen. Long-term use under such conditions can easily cause discomfort to the user, which can cause visual fatigue or dizziness in mild cases, and even cause vision loss in severe cases. Improper distribution of strong and weak light on the screen or too fast changes can also cause similar problems.
[0004] In order to minimize the impact of glare, the surface of the display screen needs to be treated with anti-glare. An anti-glare coating can be added directly to the screen, or the film can be treated with anti-glare first and then bonded to the screen. When the existing process produces anti-glare film, considering the convenience and effectiveness during processing, a hardening solution containing tiny particles is generally coated on the surface of the substrate to form an anti-glare layer, such as publication numbers CN112375243A and CN113736121A. After the coated solution is dried and cured, some tiny particles float on the surface of the hardened coating to form a tiny concave-convex structure. When external light is irradiated to the surface of the screen, the directly reflected part is affected by the tiny concave-convex structure on the surface and changes from mirror reflection to diffuse reflection. The part absorbed by the screen and reflected is also affected by the tiny particles in the coating. The light that would have been directly reflected into the user's eyes is dispersed, and the light intensity is weakened, achieving an anti-glare effect.
[0005] In order to further improve the anti-glare performance or meet other optical requirements, an anti-reflection layer is usually added on the anti-glare layer by wet coating or dry sputtering to reduce the direct reflection of anti-glare light, such as publication numbers CN113699496A and CN116413841A. In addition, an anti-fingerprint layer is also added.
[0006] The existing anti-glare film generally has one or more anti-glare layers, which are formed by fully mixing and curing a hardened coating liquid with anti-glare particles. After curing, the anti-glare particles are generally evenly distributed inside and on the surface of the anti-glare layer, so that the surface of the anti-glare layer and the entire surface of the film have a concave-convex structure, which mainly achieves the anti-glare effect by converting specular reflected light into scattered light. The concave-convex structure on the surface of the film increases the surface roughness of the film while achieving the anti-glare function, which makes the film not wear-resistant and difficult to clean. Utility Model Content
[0007] In order to solve the above problems, the utility model aims to provide an anti-glare anti-reflection film to improve the wear resistance and easy-cleaning performance of the product.
[0008] Based on the above problems, the technical solution provided by the utility model is:
[0009] An anti-glare anti-reflection film, comprising:
[0010] The transparent substrate layer has a first optical surface and a second optical surface disposed opposite to each other;
[0011] An anti-glare layer, which is disposed on the first optical surface of the transparent substrate layer, wherein the anti-glare layer contains a plurality of anti-glare particles, and the anti-glare particles form a concave-convex structure on the surface of the anti-glare layer;
[0012] A filling layer, which is arranged on a side of the anti-glare layer away from the first optical surface and is used to fill the concave-convex structure on the surface of the anti-glare layer;
[0013] The anti-reflection layer is arranged on a side of the filling layer away from the anti-glare layer.
[0014] In some of the embodiments, the invention further comprises an anti-fingerprint layer disposed on a side of the anti-reflection layer away from the filling layer and a protective film disposed on a surface of the anti-fingerprint layer.
[0015] In some embodiments, the method further includes an adhesive layer disposed on the second optical surface of the transparent substrate layer and a release film disposed on a side of the adhesive layer away from the transparent substrate layer.
[0016] In some embodiments, the thickness of the anti-glare layer is 0.5-5 μm, the thickness of the filling layer is 0.5-4 μm, and the total thickness of the anti-glare layer and the filling layer is 4-6 μm.
[0017] In some embodiments, the anti-reflection layer includes a plurality of high refractive index film layers and a plurality of low refractive index film layers that are alternately arranged.
[0018] In some embodiments, the anti-reflection layer includes four low-refractive index film layers and three high-refractive index film layers, the low-refractive index film layers are SiO2 film layers, and the high-refractive index film layers are Nb2O5 film layers.
[0019] In some embodiments, the anti-reflection layer has a thickness of 0.2 to 0.35 μm.
[0020] In some embodiments, the anti-reflection layer includes a 20-30 nm SiO2 film layer, a 7-10 nm Nb2O5 film layer, a 50-55 nm SiO2 film layer, a 27-30 nm Nb2O5 film layer, a 33-36 nm SiO2 film layer, a 28-31 nm Nb2O5 film layer, and a 97-102 nm SiO2 film layer stacked in sequence.
[0021] In some embodiments, the transparent substrate layer has a thickness of 40 to 100 μm.
[0022] In some embodiments, the anti-fingerprint layer has a thickness of 2 to 10 nm.
[0023] Compared with the prior art, the advantages of the utility model are:
[0024] A filling layer is provided on the anti-glare layer to fill the concave-convex structure of the anti-glare layer, thereby reducing the overall surface roughness of the film and making the film highly wear-resistant and easy to clean compared with similar products, thereby broadening the use scenarios of the product and extending the service life of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the utility model, the drawings required for use in the description of the embodiments will be briefly introduced below. The drawings described below are only some embodiments of the utility model. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a schematic structural diagram of an anti-glare anti-reflection film embodiment of the utility model;
[0027] in:
[0028] 1. Transparent substrate layer;
[0029] 2. Anti-glare layer; 2-1. Anti-glare particles;
[0030] 3. Filling layer;
[0031] 4. Anti-reflection layer;
[0032] 5. Anti-fingerprint layer;
[0033] 6. Protective film;
[0034] 7. Adhesive layer;
[0035] 8. Release film. DETAILED DESCRIPTION
[0036] The above scheme is further described below in conjunction with specific examples. It should be understood that these examples are used to illustrate the utility model and are not limited to the scope of the utility model. The implementation conditions used in the examples can be further adjusted according to the conditions of the specific manufacturer, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0037] like Figure 1 As shown, the utility model provides an anti-glare and anti-reflection film, comprising a transparent substrate layer 1 having a first optical surface and a second optical surface arranged opposite to each other, an anti-glare layer 2 arranged on the first optical surface of the transparent substrate layer 1, a filling layer 3 arranged on the anti-glare layer 2, and an anti-reflection layer 4 arranged on the filling layer 3.
[0038] In order to improve the anti-fingerprint effect of the product, an anti-fingerprint layer 5 is provided on the side of the anti-reflection layer 4 away from the filling layer, and a protective film 6 is provided on the surface of the anti-fingerprint layer 5 to play a protective role.
[0039] In order to facilitate the use of the film product, the film product further includes an adhesive layer 7 disposed on the second optical surface of the transparent substrate layer 1 and a release film 8 disposed on the side of the adhesive layer 7 away from the transparent substrate layer 1 .
[0040] The transparent substrate layer 1 is a film substrate with a thickness of 40 to 100 μm, and can be selected from one of triacetyl cellulose film (TAC), super refractory polyester film (SRF), polycarbonate film (PC), polyethylene terephthalate film (PET), and polymethyl methacrylate (PMMA).
[0041] The anti-glare layer 2 is formed by coating an anti-glare coating liquid on the first optical surface of the transparent substrate layer 1 and curing it, and has a thickness of 0.5 to 5 μm. The anti-glare coating liquid contains a plurality of anti-glare particles 2-1. When the anti-glare coating liquid is cured on the transparent substrate layer 1, a concave-convex structure is easily formed.
[0042] The filling layer 3 is formed by coating the filling coating liquid on the surface of the anti-glare layer 2 and curing it, and is used to fill the concave-convex structure on the surface of the anti-glare layer 2, and has a thickness of 0.5 to 5 μm. The total thickness of the anti-glare layer 2 and the filling layer 3 is 1 to 9 μm, preferably 4 to 6 μm.
[0043] The anti-reflection layer 4 is formed by alternating high-refractive film layers and low-refractive film layers on the filling layer 3, wherein the film layers close to the filling layer 3 and far away from the filling layer 3 are low-refractive film layers, the high-refractive film layer is a Nb2O5 film layer, and the refractive index of the film layer after deposition is 2.25-2.40, the low-refractive film layer is a SiO2 film layer, and the refractive index of the film layer after deposition is 1.46-1.50. In this example, the anti-reflection layer includes four low-refractive film layers and three high-refractive film layers, with a thickness of 0.2-0.35 μm.
[0044] Specifically, it includes a 20-30nm SiO2 film layer, a 7-10nm Nb2O5 film layer, a 50-55nm SiO2 film layer, a 27-30nm Nb2O5 film layer, a 33-36nm SiO2 film layer, a 28-31nm Nb2O5 film layer, and a 97-102nm SiO2 film layer stacked in sequence.
[0045] The anti-fingerprint layer 5 is formed by coating the anti-fingerprint coating liquid on the surface of the filling layer, and has a thickness of 2 to 10 nm. The protective film 6 is attached to the anti-fingerprint layer 5 .
[0046] The adhesive layer 7 is formed by coating an optically transparent adhesive (OCA) on the second optical surface of the transparent substrate layer 1 and has a thickness of 15 to 40 μm. The release film 8 is attached to the adhesive layer 7 and has a thickness of 20 to 80 μm.
[0047] A method for preparing an anti-glare anti-reflection film comprises the following steps:
[0048] S1. Mix the raw materials according to the ratio to prepare an anti-glare coating liquid and a filling coating liquid;
[0049] S2, coating, baking and curing the anti-glare coating liquid on the first optical surface of the transparent substrate layer to form an anti-glare layer;
[0050] S3, coating, baking and curing the filling coating liquid on the anti-glare layer to form a filling layer;
[0051] S4, using a vacuum magnetron winding coating machine, after plasma cleaning under vacuum conditions, depositing a plurality of high refractive index film layers and a plurality of low refractive index film layers alternately on the filling layer to form an anti-reflection layer;
[0052] S5, spraying an anti-fingerprint coating liquid on the anti-reflection layer by spraying, baking and curing to form an anti-fingerprint layer and covering it with a protective film;
[0053] S6, coating an optically transparent adhesive on the second optical surface of the transparent substrate layer, and baking to form an adhesive layer;
[0054] S7. Attach a release film to the adhesive layer.
[0055] Among them, the anti-glare layer and the filling layer are coated by a micro-concave roller coating process, and a micro-concave coating machine can be used. The anti-glare coating liquid and the filling coating liquid are both light-curing coating liquids, and they still need to be baked and UV-cured after coating. The baking uses an IR tunnel furnace to heat the organic solvent in the coating liquid to volatilize. Depending on the composition of the coating liquid, the curing energy used for UV curing is 200-400mJ / cm 2 within the range.
[0056] The components of the anti-glare coating liquid in step S2 include, by weight percentage: 15% to 40% of acrylate prepolymer, 2% to 12% of acrylate monomer, 3% to 9% of photoinitiator, 0.5% to 8% of anti-glare particles, 0.5% to 8% of dispersant, 0.1% to 0.6% of antioxidant, and 50% to 78% of organic solvent.
[0057] The components of the filling coating liquid in step S2 include, by weight percentage, 15% to 40% of acrylate prepolymer, 2% to 12% of acrylate monomer, 3% to 9% of photoinitiator, 0.1% to 0.6% of antioxidant, and 50% to 78% of organic solvent. The filling coating liquid has similar components to the anti-glare coating liquid, and does not contain anti-glare particles and dispersant.
[0058] The acrylate prepolymer is one or a combination of at least two acrylic resins such as polyurethane acrylic resin, polyester acrylic resin, epoxy acrylate resin, etc. L-6902 and L-6111 produced by Guangdong Lankelu New Materials Co., Ltd. and HT-7600, HT-7602, SU-429, HP-6919, HP-6285 and CR91093 produced by Guangdong Haohui New Materials Co., Ltd. can be selected.
[0059] The acrylate monomer is one of trimethylolpropane triacrylate (TMPTA), ditrimethylolpropane tetraacrylate (DI-TMPTA), ethoxylated trimethylolpropane triacrylate (ETPAC), 1,6-hexanediol diacrylate (HDDA), or a combination of at least two thereof.
[0060] The photoinitiator is one of the commonly used photoinitiators 184, 651, 2959, 369, 907, TPO, MBF, 754, BP or a combination of at least two thereof. Preferably, a conventional photoinitiator is used together with a deep-layer photoinitiator to increase the internal curing rate of the coating and enhance the reliability of the coating.
[0061] The anti-glare particles are inorganic nanoparticles, which are one or a combination of at least two of nano-silicon dioxide, nano-titanium dioxide, nano-aluminum oxide, nano-zirconium oxide, nano-zinc oxide, and nano-calcium carbonate. The particle size of the inorganic nanoparticles is 50 to 300 nm. It is preferred that nanoparticles with a higher refractive index and nanoparticles with a lower refractive index are mixed with the anti-glare coating liquid. Under the condition of meeting the anti-glare requirements, the amount of particles is adjusted so that the refractive index of the anti-glare coating liquid is as consistent as possible with that of the filling coating liquid.
[0062] The dispersant is a nanoparticle dispersant, which is usually an unsaturated polyamine amide and a low molecular weight acidic polyester salt solution. BYK-ATU, BYK-180, BYK-2026 produced by BYK Chemical can be selected.
[0063] The antioxidant is one of the commonly used antioxidants 1010, 1076, 168, 626, PEPQ, 225, or a combination of at least two thereof.
[0064] The organic solvent is an aromatic hydrocarbon, an aliphatic hydrocarbon, an alcohol, an ester, a ketone, an amide or an ether solvent.
[0065] Example 1
[0066] Preparation of anti-glare coating liquid: 1.2 parts by weight of wetting and dispersing agent BYK-ATU and 70 parts by weight of organic solvent are mixed evenly, 1.2 parts by weight of nano-SiO2 with a particle size of 100 nm and 0.2 parts by weight of nano-Al2O3 are added, and the inorganic nanoparticles are evenly dispersed by ultrasonic dispersion for 10 minutes, and then 30 parts by weight of acrylic prepolymer HP-6919, 5 parts by weight of acrylic monomer HDDA, 3.6 parts by weight of photoinitiator 184 and 3.6 parts by weight of photoinitiator TPO, 0.3 parts by weight of antioxidant 1010 and 0.15 parts by weight of antioxidant 168 are added in sequence, and stirred evenly to obtain the anti-glare coating liquid.
[0067] Preparation of the filling coating liquid: Add 30 parts by weight of acrylic prepolymer HP-6919, 5 parts by weight of acrylic monomer HDDA, 3.6 parts by weight of photoinitiator 184 and 3.6 parts by weight of photoinitiator TPO, 0.3 parts by weight of antioxidant 1010 and 0.15 parts by weight of antioxidant 168 in 70 parts by weight of an organic solvent mixture in sequence, stir evenly to obtain the filling coating liquid.
[0068] The transparent substrate layer and the anti-glare coating liquid are put into the micro-concave coating machine, and the anti-glare layer is obtained after unwinding, coating, baking, UV curing, and winding, and the thickness is about 3.5μm. The transparent substrate layer coated with the anti-glare layer and the filling coating liquid are put into the micro-concave coating machine, and the filling layer is obtained after unwinding, coating, baking, UV curing, and winding, and the thickness is about 1.5μm.
[0069] The transparent substrate layer coated with the anti-glare layer and the filling layer is put into a vacuum magnetron winding coating machine, and the anti-reflection layer is obtained after unwinding, plasma cleaning, coating and winding. From the inside to the outside, there are 25nm SiO2 film layer, 9nm Nb2O5 film layer, 51.5nm SiO2 film layer, 28nm Nb2O5 film layer, 34.5nm SiO2 film layer, 29.5nm Nb2O5 film layer and 100nm SiO2 film layer.
[0070] The anti-fingerprint coating liquid is sprayed on the anti-reflection layer, and then baked and cured to form an anti-fingerprint layer. The protective film is laminated on the anti-fingerprint layer in a roll-to-roll manner.
[0071] An optically transparent adhesive is applied to the other side of the film substrate and baked to form an adhesive layer. A release film is applied to the adhesive layer in a roll-to-roll manner.
[0072] Example 2
[0073] In Example 2, more anti-glare particles are added to the anti-glare coating liquid.
[0074] Preparation of anti-glare coating liquid: 2.3 parts by weight of wetting and dispersing agent BYK-ATU and 70 parts by weight of organic solvent are mixed evenly, 2.3 parts by weight of nano-SiO2 with a particle size of 100 nm and 0.3 parts by weight of nano-Al2O3 are added, and the inorganic nanoparticles are evenly dispersed by ultrasonic dispersion for 10 minutes, and then 30 parts by weight of acrylic prepolymer HP-6919, 5 parts by weight of acrylic monomer HDDA, 3.6 parts by weight of photoinitiator 184 and 3.6 parts by weight of photoinitiator TPO, 0.3 parts by weight of antioxidant 1010 and 0.15 parts by weight of antioxidant 168 are added in sequence, and stirred evenly to obtain the anti-glare coating liquid.
[0075] Preparation of the filling coating liquid: Add 30 parts by weight of acrylic prepolymer HP-6919, 5 parts by weight of acrylic monomer HDDA, 3.6 parts by weight of photoinitiator 184 and 3.6 parts by weight of photoinitiator TPO, 0.3 parts by weight of antioxidant 1010 and 0.15 parts by weight of antioxidant 168 in 70 parts by weight of an organic solvent mixture in sequence, stir evenly to obtain the filling coating liquid.
[0076] The film substrate and the anti-glare coating liquid are put into the micro-concave coating machine, and the anti-glare layer is obtained after unwinding, coating, baking, UV curing, and winding, and the thickness is about 3.5μm. The film substrate coated with the anti-glare layer and the filling coating liquid are put into the micro-concave coating machine, and the filling layer is obtained after unwinding, coating, baking, UV curing, and winding, and the thickness is about 1.5μm.
[0077] The film substrate coated with the anti-glare layer and the filling layer is put into a vacuum magnetron winding coating machine. After unwinding, plasma cleaning, coating and winding, the anti-reflection layer is obtained. From the inside to the outside, there is a 25nm SiO2 film layer, a 9nm Nb2O5 film layer, a 51.5nm SiO2 film layer, a 28nm Nb2O5 film layer, a 34.5nm SiO2 film layer, a 29.5nm Nb2O5 film layer, and a 100nm SiO2 film layer.
[0078] The anti-fingerprint coating liquid is sprayed on the anti-reflection layer, and then baked and cured to form an anti-fingerprint layer. The protective film is laminated on the anti-fingerprint layer in a roll-to-roll manner.
[0079] An optically transparent adhesive is applied to the other side of the film substrate and baked to form an adhesive layer. A release film is applied to the adhesive layer in a roll-to-roll manner.
[0080] Comparative Example 1
[0081] The other aspects are the same as those of Example 1, except that no anti-glare layer is applied, and only a filling layer is applied.
[0082] Preparation of the filling coating liquid: Add 30 parts by weight of acrylic prepolymer HP-6919, 5 parts by weight of acrylic monomer HDDA, 3.6 parts by weight of photoinitiator 184 and 3.6 parts by weight of photoinitiator TPO, 0.3 parts by weight of antioxidant 1010 and 0.15 parts by weight of antioxidant 168 in 70 parts by weight of an organic solvent mixture in sequence, stir evenly to obtain the filling coating liquid.
[0083] The film substrate and the filling coating liquid are put into the micro-concave coating machine, and after unwinding, coating, baking, UV curing and winding, the filling layer is obtained with a thickness of about 5μm.
[0084] The film substrate coated with the filling layer is put into a vacuum magnetron winding coating machine, and the anti-reflection layer is obtained after unwinding, plasma cleaning, coating and winding.
[0085] The anti-fingerprint coating liquid is sprayed on the anti-reflection layer, and then baked and cured to form an anti-fingerprint layer. The protective film is laminated on the anti-fingerprint layer in a roll-to-roll manner.
[0086] An optically transparent adhesive is applied to the other side of the film substrate and baked to form an adhesive layer. A release film is applied to the adhesive layer in a roll-to-roll manner.
[0087] Comparative Example 2
[0088] The other aspects are the same as those of Example 1, except that no filling layer is applied, and only an anti-glare layer is applied.
[0089] Preparation of anti-glare coating liquid: 1.2 parts by weight of wetting and dispersing agent BYK-ATU and 70 parts by weight of organic solvent are mixed evenly, 1.2 parts by weight of nano-SiO2 with a particle size of 100 nm and 0.2 parts by weight of nano-Al2O3 are added, and the inorganic nanoparticles are evenly dispersed by ultrasonic dispersion for 10 minutes, and then 30 parts by weight of acrylic prepolymer HP-6919, 5 parts by weight of acrylic monomer HDDA, 3.6 parts by weight of photoinitiator 184 and 3.6 parts by weight of photoinitiator TPO, 0.3 parts by weight of antioxidant 1010 and 0.15 parts by weight of antioxidant 168 are added in sequence, and stirred evenly to obtain the anti-glare coating liquid.
[0090] The film substrate and the anti-glare coating liquid are put into a micro-concave coating machine, and the anti-glare layer is obtained after unwinding, coating, baking, UV curing and winding, with a thickness of about 5 μm.
[0091] The film substrate coated with the anti-glare layer is put into a vacuum magnetron winding coating machine, and the anti-reflection layer is obtained after unwinding, plasma cleaning, coating and winding.
[0092] The anti-fingerprint coating liquid is sprayed on the anti-reflection layer, and then baked and cured to form an anti-fingerprint layer. The protective film is laminated on the anti-fingerprint layer in a roll-to-roll manner.
[0093] An optically transparent adhesive is applied to the other side of the film substrate and baked to form an adhesive layer. A release film is applied to the adhesive layer in a roll-to-roll manner.
[0094] Performance Testing
[0095] During the test, the release film on the second optical surface of the transparent substrate layer was torn off and the film was evenly attached to the glass surface. The protective film was then torn off for testing. The glass used was 0.4mm thick Corning fifth-generation Gorilla Glass.
[0096] Transmittance, haze: Refer to GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics" to test transmittance and haze.
[0097] Surface roughness: Refer to GB / T 14234-1993 "Surface roughness of plastic parts" standard test surface roughness parameters profile arithmetic mean deviation Ra and profile maximum height Rz.
[0098] Wear resistance: Using 0000# steel wool, contact area 20mm×20mm, load 500g, stroke 40mm, 500cycles, 60cycles / min, the wear resistance of the film is judged by detecting whether there are scratches on the surface of the diaphragm and the change of water drop angle data before and after the wear test.
[0099] Water contact angle: Refer to GB / T 30693-2014 "Measurement of contact angle of plastic film with water" standard to test water contact angle.
[0100] Easy to clean: The color difference when wiping the artificial fingerprint liquid on the sample surface is used to judge whether it is clean, and then the easy to clean of the sample is evaluated.
[0101] 1. Drop 2.0 μL of artificial fingerprint liquid (oleic acid) on the surface of the film and press it with a 30 Shore hardness silicone pad to spread it into a circle with a diameter of 11 mm;
[0102] 2. Place the weight wrapped with the scouring pad flat on the film surface and slide it horizontally to make it completely slide over the part coated with the artificial fingerprint liquid. The scouring pad is 3M JAPAN Scotch-Brite No.5000, the contact surface of the weight is 40mm×70mm, and the weight is 500g;
[0103] 3. Measure the chromaticity of the sample before applying the artificial fingerprint liquid, and measure the chromaticity of the sample again after applying the artificial fingerprint liquid. Repeat the wiping and measurement until the absolute value of the color difference ΔE before and after applying the artificial fingerprint liquid is less than or equal to 0.3. Konica Minolta CM-700d spectrophotometer is used to measure the chromaticity.
[0104] The test results of Examples 1, 2 and Comparative Examples 1, 2 are shown in Table 1.
[0105] Table 1 Test data
[0106]
[0107]
[0108] It can be seen from the test results in Table 1 that the anti-glare anti-reflection film of the utility model takes into account both the anti-glare effect and the easy-to-clean performance.
[0109] Comparative Example 1 is a film with only anti-reflection effect but no anti-glare effect. The improved anti-glare film (Example 1, Example 2) has improved anti-glare performance, while the wear resistance and easy cleaning performance are similar to the film with no anti-glare function and only anti-reflection effect (Comparative Example 1).
[0110] Comparative Example 2 is similar to the existing anti-glare films on the market, and has anti-glare and anti-reflection effects. Its anti-glare layer is usually formed by curing one or more hardened coating liquids mixed with anti-glare particles, and has the functions of anti-glare and improving hardness, and an anti-reflection layer is added on the anti-glare layer.
[0111] Compared with the anti-glare film without an additional filling layer (Comparative Example 2), the anti-glare film with an additional filling layer (Example 1 and Example 2) has a smaller reduction in the water drop angle before and after the wear resistance test when the anti-glare performance is similar to the optical performance, that is, the wear resistance is improved, and the color difference in the easy-to-clean test after applying artificial fingerprint liquid is also reduced, and the color difference is reduced to below 0.3 in the first step of wiping, that is, it is easier to clean.
[0112] The utility model improves the shortcomings of existing products such as poor wear resistance and difficulty in cleaning by adding an additional filling layer to the anti-glare layer. The additional filling layer fills the concave-convex structure formed by adding anti-glare particles to the anti-glare layer to a certain extent, reduces the surface roughness of the film, improves the wear resistance of the film and makes it easier to clean, but also weakens its ability to disperse the light directly reflected from the screen surface.
[0113] The utility model mainly achieves the anti-glare effect by dispersing the light absorbed and reflected by the screen rather than the light directly reflected by the screen surface. The light reflected into the user's eyes is composed of two parts: the light directly reflected by the screen surface and the light absorbed and reflected by the screen. Compared with the coating of anti-reflection coating, magnetron sputtering coating can plate an anti-reflection layer with a stronger anti-reflection effect. After the sputtering deposition of the anti-reflection layer, the intensity of the light directly reflected by the screen surface is greatly weakened, and the light absorbed and reflected by the screen becomes the main factor causing glare. At this time, the difference in refractive index between the anti-glare particles added to the anti-glare layer and the hardened resin is used to form internal diffusion anti-glare, which can effectively disperse the light absorbed and reflected by the screen.
[0114] The above examples are only for illustrating the technical concept and features of the utility model, and their purpose is to enable people familiar with the technology to understand the content of the utility model and implement it accordingly, and they cannot be used to limit the protection scope of the utility model. Any equivalent changes or modifications made according to the spirit of the utility model should be included in the protection scope of the utility model.
Claims
1. An anti-glare anti-reflection film, characterized in that: include: The transparent substrate layer has a first optical surface and a second optical surface disposed opposite to each other; An anti-glare layer, which is disposed on the first optical surface of the transparent substrate layer, wherein the anti-glare layer contains a plurality of anti-glare particles, and the anti-glare particles form a concave-convex structure on the surface of the anti-glare layer; A filling layer, which is arranged on a side of the anti-glare layer away from the first optical surface and is used to fill the concave-convex structure on the surface of the anti-glare layer; The anti-reflection layer is arranged on a side of the filling layer away from the anti-glare layer.
2. The anti-glare anti-reflection film according to claim 1, characterized in that: It also includes an anti-fingerprint layer arranged on a side of the anti-reflection layer away from the filling layer and a protective film arranged on the surface of the anti-fingerprint layer.
3. The anti-glare anti-reflection film according to claim 2, characterized in that: The thickness of the anti-fingerprint layer is 2-10 nm.
4. The anti-glare anti-reflection film according to claim 2, characterized in that: The invention also includes an adhesive layer disposed on the second optical surface of the transparent substrate layer and a release film disposed on a side of the adhesive layer away from the transparent substrate layer.
5. The anti-glare anti-reflection film according to claim 1, characterized in that: The thickness of the anti-glare layer is 0.5-5 μm, the thickness of the filling layer is 0.5-4 μm, and the total thickness of the anti-glare layer and the filling layer is 4-6 μm.
6. The anti-glare anti-reflection film according to claim 1, characterized in that: The anti-reflection layer includes a plurality of high-refractive index film layers and a plurality of low-refractive index film layers which are arranged alternately.
7. The anti-glare anti-reflection film according to claim 6, characterized in that: The anti-reflection layer includes four low-refractive index film layers and three high-refractive index film layers, the low-refractive index film layers are SiO2 film layers, and the high-refractive index film layers are Nb2O5 film layers.
8. The anti-glare anti-reflection film according to claim 7, characterized in that: The thickness of the anti-reflection layer is 0.2-0.35 μm.
9. The anti-glare anti-reflection film according to claim 8, characterized in that: The anti-reflection layer includes a 20-30nm SiO2 film layer, a 7-10nm Nb2O5 film layer, a 50-55nm SiO2 film layer, a 27-30nm Nb2O5 film layer, a 33-36nm SiO2 film layer, a 28-31nm Nb2O5 film layer, and a 97-102nm SiO2 film layer stacked in sequence.
10. The anti-glare anti-reflection film according to claim 1, characterized in that: The thickness of the transparent substrate layer is 40 to 100 μm.
Citation Information
Patent Citations
High-wear-resistance and low-flash-point anti-glare film and preparation method thereof
CN112375243A
Anti-dazzle low-reflection film and manufacturing method thereof
CN113699496A
Anti-glare film and preparation method thereof
CN113736121A
Anti-dazzle low-reflection film and preparation method thereof
CN116413841A